PERAN FINTECH DALAM MENINGKATKAN INKLUSI PASAR MODAL SYARIAH DI INDONESIA - Nia Safira Ramadhanty Pane; Reni Ria Armayani Hasibbuan; Asryatun Nisa BR Ginting; Ezika Aquilera Sitio (INTERNATIONAL, Journal of Sharia Business Management, 2025)
The development of financial technology (fintech) has brought significant changes to the financial system, including the Islamic capital market sector in Indonesia. The capital market plays a crucial role as a means of fund mobilization and allocation for society while supporting sustainable economic growth. However, the level of inclusion in the Islamic capital market still faces various challenges, such as limited access, low financial literacy, and complex investment procedures. This study aims to analyze the role of fintech in enhancing the inclusion of the Islamic capital market in Indonesia. The research method employed is a literature review by examining scholarly journals, books, official reports, and regulations related to fintech, financial inclusion, and the Islamic capital market. The findings indicate that fintech plays an important role in expanding public access to Islamic investment through transaction convenience, reduced initial capital barriers, and improved efficiency and transparency. Furthermore, fintech encourages greater participation of retail investors while maintaining compliance with Sharia principles as stipulated in relevant fatwas and regulations. Therefore, fintech has significant potential to support the enhancement of Islamic capital market inclusion in Indonesia, particularly when accompanied by improved Islamic financial literacy and strengthened regulatory frameworks..